(untitled) (Studia theodisca, 2021)
This article attempts to explore the intimate yet complicated friendship between Stefan Zweig and Joseph Roth through their exchange of letters. Their personal correspondence has always been regarded as a valuable resource for interpreting their works and for documenting the life of intellectuals during the National Socialist period. However, the relevance of their correspondence does not lie only in its literary and historical testimony, since it is also strictly related to its auto/biographical aspects. Adopting this perspective, the article offers a reading of the letters both as an autobiographical portrait of Zweig and Roth and as a distant narrative of their friendship, conceived as the only possible homeland for the two writers in exile.